Measuring Leadership Behaviour in a Global Industry : Sand Cone Model of Transformational Leadership and People, Process and Goal Model - Ha-Vikström, Thanh (Vaasan yliopisto, 2018)
It has long been understood that leadership behaviour plays a crucial role in keeping employees happy and loyal, which in turn directly contributes to organizational success. But, in today’s increasingly competitive world, how is it possible to distinguish a great leader among a crowded workforce? The main purpose of this dissertation is to explore ways of measuring different dimensions of leadership behaviour as perceived by leaders themselves within a global organization. This dissertation is composed of five peer-reviewed publications in which qualitative, quantitative and triangulation approaches were employed to provide a more comprehensive treatment of research problems. This dissertation offers two models with feasible processes and techniques, which can evaluate and measure different dimensions of leadership behaviour: the sand cone model (SCM) of transformational leadership and the people, process and goal model (PPGM). The first model focuses on the effectiveness of transformational leadership behaviour, while the latter identifies leaders’ focus areas and helps to develop leaders’ strengths and priorities, as well as less cultivated abilities. Both of the models extend the theories of leadership behaviour. The SCM can be used for short-term visions, whereas the PPGM is best suited for long-term endeavours. Each leader is encouraged to utilize the SCM to enhance their current leadership skills, while higher-level management teams are recommended to use the PPGM to define the healthiest balance between different leadership focus areas for their own organizational success.

On jo pitkään ymmärretty, että johtaminen vaikuttaa merkittävästi henkilöstön työtyytyväisyyteen ja lojaaliuteen työnantajaa kohtaan, mikä puolestaan vaikuttaa suoraan organisaation menestykseen. Mutta miten voi yhä kovemmin kilpaillussa yritysmaailmassa tunnistaa hyvän johtajan suuresta joukosta? Tämä väitöskirja tutkii tapoja mitata johtamiskäyttäytymisen eri ulottuvuuksia siten kuin johtajat itse ne kokevat globaalissa organisaatiossa. Väitöskirja koostuu viidestä vertaisarvioidusta julkaisusta, joissa laadullisia, määrällisiä ja monimenetelmällisyyttä hyödyntäviä menetelmiä on käytetty tutkimusongelmien kattavaan tarkasteluun. Väitöskirjassa esitetään kaksi johtamiskäyttäytymisen eri ulottuvuuksia arvioivaa ja mittaavaa mallia sekä niihin liittyvät prosessit ja tekniikat. Kyseessä ovat muuntavan johtajuuden Sand Cone -malli (SCM) sekä People, Process and Goal -malli (PPG). Ensimmäinen malli keskittyy transformationaalisen eli muuntavan johtajuuden tehokkuuden tarkasteluun, kun taas jälkimmäinen malli tunnistaa johtamistyön painopistealueita ja auttaa kehittämään johtajien vahvuuksia ja osaamista, mutta myös vähemmän kehittyneitä kyvykkyyksiä. Molemmat mallit laajentavat johtamiskäyttäytymisen teoriaperustaa. Sand Cone -mallia voidaan käyttää erityisesti lyhyen aikavälin hahmotuksiin, kun taas People, Process and Goal -malli soveltuu parhaiten pitkäaikaisiin kehitystehtäviin. Johtajille suositellaan Sand Cone -mallin hyödyntämistä olemassa olevien johtamisvalmiuksiensa kehittämiseen. Korkean tason johtoryhmille suositellaan People, Process and Goal -mallin käyttämistä eri johtamisalueiden tasapainon määrittelyyn ja sitä kautta organisaation monipuoliseksi menestykseksi.
Keywords: johtamiskäyttäytyminen; leadership behaviour; muuntava johtajuus; transformational leadership; Sand Cone -malli; Sand Cone Model; johtaminen; johtajuus